2012
DOI: 10.1155/2012/436959
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mesotherapy in Musculoskeletal Pain: Opinions from the Italian Society of Mesotherapy

Abstract: Mesotherapy is the injection of active substances into the surface layer of the skin. This method allows a slower spread, higher levels, and longer lasting effects of drugs in the tissues underlying the site of injection (skin, muscle, and joint) compared with those following intramuscular injection. This technique is useful when a local pharmacological effect is required and relatively high doses of drug in the systemic circulation are not. Mesotherapy should only be undertaken following a complete clinical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 37 publications
1
64
0
7
Order By: Relevance
“…In the case that we presented, mesotherapy allowed to control pain, avoiding adverse effects of oral therapy, with a weekly treatment. We suggested to insert the mesotherapy in the scheme of treatment of patients who need to reduce the dosages of systemic drugs, or who cannot take them because of a risk benefit ratio unfavorable, and to get a drug-sparing effect [7,9]. When performing mesotherapy, attention must be paid on certain aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case that we presented, mesotherapy allowed to control pain, avoiding adverse effects of oral therapy, with a weekly treatment. We suggested to insert the mesotherapy in the scheme of treatment of patients who need to reduce the dosages of systemic drugs, or who cannot take them because of a risk benefit ratio unfavorable, and to get a drug-sparing effect [7,9]. When performing mesotherapy, attention must be paid on certain aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the pharmacological effect of drugs, it was also suggested that the reflex effect produced by the needles can induce clinical benefits [8]. In fact, many studies reported pain relief in patients with several musculoskeletal or posttraumatic conditions [9]. Mesotherapy is now well defined as a minimally invasive technique, useful to reduce dose of active compounds, a rapid onset and a prolonged duration of action [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 Os efeitos adversos dos AINEs por via sistémica 3 , nomeadamente toxicidade gastrointestinal, disfunção renal, complicações cardiovasculares, especialmente em idosos, faz da mesoterapia, caso bem tolerada, uma técnica alternativa no combate à dor.…”
unclassified
“…3 Binaglia, em 1981, revelou que microinjeções de cetoprofeno de sódio intradérmicas tinham uma ação mais duradoura do que a respetiva injeção intramuscular, demonstrando igualmente que, quando injetado a uma profundidade superior a 10mm, permanecia menos tempo nos tecidos, chegando mesmo a atingir a circulação sistémica.…”
unclassified
“…Jedną z powszechnie znanych metod jest mezoterapia, zwana również intradermoterapią, polegająca na śródskórnych iniekcjach aktywnych substancji leczniczych. W latach 70. minionego stulecia francuski lekarz Michel Pastor po raz pierwszy zaczął stosować tę metodę w dermatologii estetycznej, a obecnie wykorzystuje się ją do ostrzykiwania twarzy oraz innych okolic ciała -zarówno w celach leczniczych, jak i w profilaktyce przeciwstarzeniowej [11][12][13].…”
unclassified